A Circular Bioresource Approach: Converting Water Hyacinth into Compost for Improved Soil Fertility and Yam Production in Tropical Wetlands - Sari, Nukhak Nufita; Abduh, Andin Muhammad; Mulyawan, Ronny; Ellya, Hikma; Apriani, Rila Rahma; Nurlaila, Nurlaila; Masganti, Masganti; Yusran, Fadly Hairannoor (Fakultas Pertanian Universitas Padjadjaran, 2026)
Tropical wetland ecosystems face challenges due to acidic soils, poor drainage, and fluctuating water levels, limiting soil fertility and agricultural productivity. However, the abundant biomass of water hyacinth (Eichhornia crassipes) offers a potential in-situ organic resource that can be recycled through composting, supporting a circular nutrient approach by returning nutrients from aquatic environments to agricultural soils. The objective of this research was to evaluate the effects of composted water hyacinth on soil chemical properties and crop performance of the Alabio water yam (Dioscorea alata L.) grown in tropical freshwater swamps. Water hyacinth compost with a C/N ratio of 15.55 and enriched with essential nutrients was applied at three rates: 30, 35, and 40 ton/ha, using a randomized block design. Soil chemical properties and tuber yield were analyzed by ANOVA and LSD tests, and regression analysis was performed to identify the key factors influencing yield. The compost significantly improved soil total-N, total-P, and available-P, while increasing soil organic-C and cation-exchange capacity. The highest tuber yield, 7.4 kg/m², was obtained at the 40 ton/ha compost rate, representing a 21% increase compared with the lowest rate. Regression analysis (R² = 0.904) confirmed that soil available phosphorus was the primary determinant of yield improvement. This research provides empirical evidence that water hyacinth compost amendment can simultaneously enhance soil fertility and yam yield in tropical wetland systems.